The role of isothiocyanate-rich plants and supplements in neuropsychiatric disorders: a review and update - Ramakrishnan, Monica; Fahey, Jed W.; Zimmerman, Andrew W.; Zhou, Xinyi; Panjwani, Anita A. (Frontiers in Nutrition, 2024)
Neuroinflammation in response to environmental stressors is an important common pathway in a number of neurological and psychiatric disorders. Responses to immune-mediated stress can lead to epigenetic changes and the development of neuropsychiatric disorders. Isothiocyanates (ITC) have shown promise in combating oxidative stress and inflammation in the nervous system as well as organ systems. While sulforaphane from broccoli is the most widely studied ITC for biomedical applications, ITC and their precursor glucosinolates are found in many species of cruciferous and other vegetables including moringa. In this review, we examine both clinical and pre-clinical studies of ITC on the amelioration of neuropsychiatric disorders (neurodevelopmental, neurodegenerative, and other) from 2018 to the present, including documentation of protocols for several ongoing clinical studies. During this time, there have been 15 clinical studies (8 randomized controlled trials), most of which reported on the effect of sulforaphane on autism spectrum disorder and schizophrenia. We also review over 80 preclinical studies examining ITC treatment of brain-related dysfunctions and disorders. The evidence to date reveals ITC have great potential for treating these conditions with minimal toxicity. The authors call for well-designed clinical trials to further the translation of these potent phytochemicals into therapeutic practice.